Monetary Policy And Economic Growth In Nigeria: Evidence From Nigeria - Inam, Uduakobong S.; Ime, Blessing Sunday (Advances in Social Sciences Research Journal, 2017)
annual data covering the period of 1970 to 2012. Specifically, it seeks to: analyse the relationship between money supply and economic growth in Nigeria; determine the nature and direction of causality between money supply and economic growth. The study employs the Ordinary Least Square (OLS) techniques and the granger causality test. The result indicates a positive and insignificant relationship between money supply and economic growth. Furthermore, it indicates no causality between money supply and economic growth. The study recommends that government and relevant monetary authorities should ensure that money supply levels are effectively and efficiently monitored, managed and controlled so as to enhance, promote and achieve economic growth in Nigeria.